Ruxolitinib discontinuation in polycythemia vera: Patient characteristics, outcomes, and salvage strategies from a large multi-institutional database. (October 2021) - Tremblay, Douglas; Ronner, Lukas; Podoltsev, Nikolai; Gotlib, Jason; Heaney, Mark; Kuykendall, Andrew; O'Connell, Casey; Shammo, Jamile M.; Fleischman, Angela; Mesa, Ruben; Yacoub, Abdulraheem; Hoffman, Ronald; et al.
Highlights: This is the first analysis of outcomes after ruxolitinib discontinuation in PV. Adverse events were the primary reason for ruxolitinib discontinuation. After discontinuation, no patients experienced a thrombotic event. Few patients received salvage cytoreductive therapy. Abstract: Ruxolitinib is approved for the treatment of patients with polycythemia vera (PV) who are intolerant or resistant to hydroxyurea. While ruxolitinib discontinuation in myelofibrosis is associated with dismal outcomes, the analogous experience in PV has not been reported. Using a large, multi-institutional database of PV patients, we identified 93 patients with PV who were treated with ruxolitinib, of whom 22 discontinued therapy. Adverse events were the primary reason for discontinuation. After a median follow-up of 18.2 months following ruxolitinib discontinuation, no patients experienced a thrombotic event. One patient died 20.8 months after discontinuation. As compared with the 71 patients who were still receiving treatment with ruxolitinib at last follow up, patients who discontinued ruxolitinib were older at time of treatment initiation (67.5 versus 64.8 years, p = 0.0058), but had similar patient and disease characteristics. After discontinuation, only 4 patients (18 %) received subsequent cytoreductive therapy, including hydroxyurea in one patient and pegylated interferon α-2a in three patients. In stark contrast to the experience in myelofibrosis, discontinuation of ruxolitinib in PV was associated with generally favorable outcomes. However, there is a lack of available salvage therapies, highlighting the need for further therapeutic development in PV.